Causes and consequences of anterior pharyngeal pouch after total laryngectomy. Issue 2 (July 2014) - Anderson, S; Hogan, D; Panizza, B
Abstract Objectives: To assess the frequency of anterior pharyngeal pouch formation after total laryngectomy, and to discuss the causes and consequences of anterior pharyngeal pouch formation. Study design: A prospective, observational study of 43 patients undergoing total laryngectomy. Methods: Data collected included laryngeal defect closure type, tumour staging and demographic information. A barium swallow was performed on day 7–14 after surgery to assess for anterior pharyngeal pouch formation and fistula formation. Results: The incidence of anterior pharyngeal pouch formation was 47 per cent. Patients who did not have an anterior pharyngeal pouch on swallow imaging assessment were less likely to develop a pharyngo-cutaneous fistula. There was no statistically significant association between laryngeal defect closure type and anterior pharyngeal pouch formation. Conclusion: The anterior pharyngeal pouch is a dynamic phenomenon best investigated with a fluoroscopic swallow imaging study. Its causes are multi-factorial. Absence of an anterior pharyngeal pouch appears to confer protection against pharyngo-cutaneous fistula formation, hastening commencement of adjuvant therapy and an oral diet.